Caracterización experimental del campo lejano de los vertidos de salmuera al mar. Issue 2 (1st July 2016) - Pérez-Díaz, B.; Palomar, P.; Castanedo, S.; Álvarez, A.
Abstract: Brine discharges are flows driven by the density difference between the environmental fluid, the seawater, and the discharge. They are generated by the rejected water of desalination plants, hence they are common in nature nowadays, and have a great impact on protected ecosystems. Two well-distinguished regions can be differentiated in the study of the behaviour of these discharges: the near field region, located in the vicinity of the discharge point and characterised by high dilution rates due to the turbulence effects; and the far field region, where the brine turns into a gravity current that flows down the seabed with low dilution rates. The behaviour of these gravity currents is dependent on the brine discharge characteristics, the bathymetry and the hydrodynamic conditions of the receiving water. This work shows the experimental characterization of the far field region of brine discharges through advanced non-intrusive laser optical techniques PIV (Particle Image Velocimetry) and PLIF (Planar Laser Induced Fluorescence), under controlled laboratory conditions. By means of synchronized PIV-PLIF techniques, high-quality accurate instantaneous measurements of velocity and concentration are obtained. The aim of these experiments is to study the quasi-steady flow properties of gravity currents generated by a constant flux release mimicking the far field of brine discharges. Different experimental set-upswith different initial conditions (flow rate, thickness, slope, salt concentration) were carried out in a 3 × 3 × 1 m tank. Through PIV-PLIF analysis, conclusions about the influence of these variables on the mixing at the interface between fluids have been obtained. As an example, keeping constant the rest of variables, steeper slopes and higher flow rates favour dilution, reaching stable entrainment values close to 5·10-2 against base case (with slope near zero and lower flow rate) values close to 2·10-2. In addition, a high resolution and quality experimental database has been generated, which will allow to calibrate/validate both simplified tools, based on systems of integrated equations, and advanced hydrodynamic modelling tools.